(untitled) (مجلة المنصور, 2022)
Broken links in a Web site is common problem on the Internet today. It inconvenience visitors, inhibits proper navigation of a site, prohibit access to Web site content and reduce the productivity of Web professionals. Furthermore, as our society becomes more dependent upon the Internet, ensuring that links are accurately, efficiently and timely maintained will assume a heightened priority. The aim of this paper is to find a method that test all website pages links, and gives a detailed report about all found broken links, whether these links were text links or image links.